Notulae ad floram Sloveniae - Podgornik, Gregor (Hladnikia (Ljubljana), 2005)
Nova nahajališča v zahodni Sloveniji
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation